Mortality risk in a nationwide cohort of individuals with tic disorders and with tourette syndrome. Issue 4 (24th March 2017) - Meier, Sandra M.; Dalsgaard, Søren; Mortensen, Preben B.; Leckman, James F.; Plessen, Kerstin J.
ABSTRACT: Background : Few studies have investigated mortality risk in individuals with tic disorders. Methods : We thus measured the risk of premature death in individuals with tic disorders and with Tourette syndrome in a prospective cohort study with 80 million person‐years of follow‐up. We estimated mortality rate ratios and adjusted for calendar year, age, sex, urbanicity, maternal and paternal age, and psychiatric disorders to compare individuals with and without tic disorders. Results : The risk of premature death was higher among individuals with tic disorders (mortality rate ratio, 2.02; 95% CI, 1.49‐2.66) and with Tourette syndrome (mortality rate ratio, 1.63; 95% CI, 1.11‐2.28) compared with controls. After the exclusion of individuals with comorbid attention‐deficit/hyperactivity disorder, obsessive‐compulsive disorder, and substance abuse, tic disorder remained associated with increased mortality risk (mortality rate ratio, 2.30; 95% CI, 1.57‐3.23), as did also Tourette Syndrome (mortality rate ratio, 1.81; 95% CI, 1.11–2.75). Conclusions : These results are of clinical significance for clinicians and advocacy organizations. Several factors may contribute to this increased risk of premature death, and more research mapping out these factors is needed. © 2017 International Parkinson and Movement Disorder Society